A comparative study between combination of topical metronidazole and diltiazem vs diltiazem alone in treatment of acute anal fissure - Jain, Abhishek; Khan, Rafat; Garg, Nitin (International Surgery Journal, 2025)
Background: Anal fissure is a common anorectal condition characterized by severe pain and bleeding. Topical diltiazem is a widely used treatment, but its efficacy can be enhanced by combining it with metronidazole. To compare the efficacy of topical diltiazem with metronidazole versus topical diltiazem alone in treating acute anal fissure. Methods: This non-randomized clinical trial was conducted among 174 patients with acute anal fissure. Patients were allocated into two groups: combination group (topical diltiazem with metronidazole) and diltiazem alone group. Patients were followed up at 1, 2 and 4 weeks. Results: The combination group showed significant pain reduction (7.30±0.89 to 0.48±0.21, p<0.05) and higher healing rates compared to the diltiazem alone group. The requirement for surgery was significantly lower in the combination group (8% vs 20.7%, p<0.05). Conclusions: The combination of topical diltiazem with metronidazole is a safe and effective treatment for acute anal fissure, offering rapid and sustained pain relief, improved healing rates and reduced need for surgery.